MODELS OF REALIZATION OF COMPLEX CONTROL-CALCULATION METHOD OF AIRCRAFT ENGINES PROFOUND DIAGNOSING - Чоха, Ю. (Science-based technologies, 2012)
We consider some methodological steps of the implementation of the universal integrated method to provide enhanced operational assessment of the current technical condition of modern aircraft engines.